Radical curing composition and cured product

JP7634468B2Active Publication Date: 2025-02-21SHIN ETSU CHEMICAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021198138
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-06
Publication Date
2025-02-21
Estimated Expiration
2041-12-06

AI Technical Summary

Benefits of technology

【0017】 本発明のラジカル硬化型組成物は、ラジカル硬化により低温での硬化が可能であるため、量子ドットのバインダー材料として有用であり、本発明のラジカル硬化型組成物を硬化して得られる硬化物は優れた透明性と良好な硬度を有するため、LED素子等の封止材や波長変換フィルター等の用途に有用である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007634468000001
    Figure 0007634468000001
  • Figure 0007634468000002
    Figure 0007634468000002
  • Figure 0007634468000003
    Figure 0007634468000003
Patent Text Reader

Abstract

To provide a radical curable composition which is curable at low temperatures, and enables production of a cured product excellent in hardness and light permeability.SOLUTION: A radical curable composition contains (A) a compound that is an addition reaction product of (a) a compound represented by formula (1) and / or a compound in which a silyl group is added to 1,3,5-positions in formula (1), and (b) a compound having one or more (meth)acrylic groups and addition reactive carbon-carbon double bond-containing groups other than the (meth)acrylic group in one molecule, and having no polycyclic hydrocarbon skeleton, and that is one or more (meth)acrylic groups in one molecule, and (B) a polymerization initiator. In formula (1), R1 is independently a substituted or unsubstituted monovalent hydrocarbon group which does not include an addition reactive carbon-carbon double bond-containing group, and has 1 to 12 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a radically curable composition and a cured product thereof. [Background technology]

[0002] Quantum dots, which have excellent wavelength conversion efficiency, have been attracting attention as wavelength conversion materials for light-emitting diodes (LEDs). Quantum dots are vulnerable to moisture, so they need to be sealed with a material with high gas barrier properties. On the other hand, quantum dots often contain catalytic poisons for addition reactions, and when addition-curing compositions are used as binder materials for quantum dots, there are cases where curing failure occurs. Furthermore, quantum dots have low heat resistance, so they have difficulty withstanding the curing conditions of addition-curing materials.

[0003] In response to this problem, a radical curing composition has been proposed that contains a polycyclic hydrocarbon skeleton and a silphenylene skeleton with high gas barrier properties and that can be cured at low temperatures (Patent Document 1). Although the polycyclic hydrocarbon skeleton is essential for obtaining a cured product with excellent hardness, crack resistance, and heat resistance, there has been a demand for further improvement in the hardness of the obtained cured product. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2021-116347 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a radical curable composition that can be cured at low temperatures and gives a cured product having excellent hardness and light transmittance. [Means for solving the problem]

[0006] In order to solve the above problems, the present invention provides A radical curable composition, (A) (a) a compound represented by the following general formula (1) and / or a compound represented by the following general formula (2), (b) A compound having one or more (meth)acrylic groups and one or more addition-reactive carbon-carbon double bond-containing groups other than (meth)acrylic groups in one molecule, and having no polycyclic hydrocarbon skeleton. and a compound having one or more (meth)acryl groups in one molecule, (B) Polymerization initiator The present invention provides a radical curing composition comprising: [ka] [ka] (In the formula, R 1 are independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms that does not contain an addition-reactive carbon-carbon double bond-containing group, or an alkoxy group having 1 to 6 carbon atoms.

[0007] The radically curable composition of the present invention can be cured at low temperatures and gives a cured product having excellent hardness and light transmittance.

[0008] In addition, the component (A) is preferably an addition reaction product of a compound represented by the following formula (3) and / or a compound represented by the following formula (4) as the component (a) and a compound represented by the following formula (5) as the component (b). [ka] [ka] [ka]

[0009] Such a radically curable composition has better curability.

[0010] The component (B) is preferably a polymerization initiator that generates radicals when exposed to ultraviolet light.

[0011] Use of such a polymerization initiator enables rapid curing at a lower temperature.

[0012] The present invention also provides a cured product obtained by curing the radically curable composition.

[0013] The cured product of the present invention has good hardness and excellent transparency, and is therefore useful for applications such as encapsulants for optical elements (such as LED elements) and filters.

[0014] The cured product preferably has a type D hardness of 80 or more.

[0015] The cured product preferably has a light transmittance of 80% or more at 400 nm in a thickness of 2 mm.

[0016] Such a cured product can be more preferably used as a sealant for optical elements, a filter, or the like. Effect of the Invention

[0017] The radically curable composition of the present invention can be cured at low temperatures by radical curing, and is therefore useful as a binder material for quantum dots. The cured product obtained by curing the radically curable composition of the present invention has excellent transparency and good hardness, and is therefore useful for applications such as encapsulating materials for LED elements and wavelength conversion filters. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] There has been a demand for a radically curable composition that can be cured at low temperatures and gives a cured product that is excellent in hardness and light transmittance.

[0019] As a result of extensive investigations aimed at achieving the above object, the present inventors have discovered that the above problems can be solved by a radically curable composition (radical curable organosilicon composition) containing components (A) and (B) described below, and have thus completed the present invention.

[0020] That is, the present invention provides: A radical curable composition, (A) (a) a compound represented by the following general formula (1) and / or a compound represented by the following general formula (2), (b) A compound having one or more (meth)acrylic groups and one or more addition-reactive carbon-carbon double bond-containing groups other than (meth)acrylic groups in one molecule, and having no polycyclic hydrocarbon skeleton. and a compound having one or more (meth)acryl groups in one molecule, (B) Polymerization initiator The radical curing composition is one which contains [ka] [ka] (In the formula, R 1 are independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms that does not contain an addition-reactive carbon-carbon double bond-containing group, or an alkoxy group having 1 to 6 carbon atoms.

[0021] The present invention will be described in detail below, but the present invention is not limited thereto.

[0022] [Radical curing composition] The radical curable composition of the present invention contains the components (A) and (B) described below as essential components. This composition may further contain any optional components as necessary in addition to the above essential components.

[0023] Each component will be described in detail below.

[0024] [Component (A)] The component (A) is (a) a compound represented by the following general formula (1) and / or a compound represented by the following general formula (2), (b) A compound having one or more (meth)acrylic groups and one or more addition-reactive carbon-carbon double bond-containing groups other than (meth)acrylic groups in one molecule, and having no polycyclic hydrocarbon skeleton. and having one or more (meth)acrylic groups in one molecule. [ka] [ka] (In the formula, R 1 are independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms that does not contain an addition-reactive carbon-carbon double bond-containing group, or an alkoxy group having 1 to 6 carbon atoms.

[0025] In the present invention, the term "(meth)acrylic group" refers to an acrylic group and / or a methacrylic group, and the term "addition reactive" refers to the property of being able to undergo an addition reaction with a hydrogen atom bonded to a silicon atom via the well-known hydrosilylation reaction.

[0026] <Component (a)> Component (a) is a compound containing a hydrogen atom bonded to a silicon atom (hereinafter referred to as "Si-H group") and is represented by the above general formula (1) and / or the above general formula (2).

[0027] R 1Specific examples of the unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms include alkyl groups having 1 to 12 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, n-hexyl, n-octyl, and n-decyl groups; cycloalkyl groups, such as cyclopentyl and cyclohexyl groups; aryl groups having 6 to 12 carbon atoms, such as phenyl and naphthyl groups; tolyl, xylyl, ethylphenyl, propyl ... Examples of such alkylaryl groups include alkylaryl groups having 7 to 12 carbon atoms, such as a phenyl group, a butylphenyl group, a pentylphenyl group, and a hexylphenyl group; aralkyl groups having 7 to 12 carbon atoms, such as a benzyl group and a phenethyl group; and halogenated alkyl groups in which one or more hydrogen atoms bonded to carbon atoms in these groups have been substituted with a halogen atom, a cyano group, an epoxy ring-containing group, or the like, such as a chloromethyl group, a 3-chloropropyl group, and a 3,3,3-trifluoropropyl group; a 2-cyanoethyl group; and a 3-glycidoxypropyl group.

[0028] Specific examples of alkoxy groups having 1 to 6 carbon atoms include a methoxy group, an ethoxy group, an n-propoxy group, an i-propoxy group, an n-butoxy group, a sec-butoxy group, a t-butoxy group, an n-pentyloxy group, an n-hexyloxy group, a cyclopentyloxy group, and a cyclohexyloxy group.

[0029] Among these, R 1 As the alkyl group, an alkyl group having 1 to 8 carbon atoms is preferable, and a methyl group is more preferable.

[0030] Specific examples of component (a) include, but are not limited to, those represented by the following formulas, where Me represents a methyl group, Et represents an ethyl group, and Ph represents a phenyl group. [ka] [ka]

[0031] The compounds represented by the above general formula (1) and the above general formula (2) may be used alone or in combination of two or more kinds.

[0032] <(b) Component> Component (b) is a compound that has one or more (meth)acrylic groups and one or more addition reactive carbon-carbon double bond-containing groups other than (meth)acrylic groups per molecule, and that does not have a polycyclic hydrocarbon skeleton.

[0033] Here, the term "addition-reactive carbon-carbon double bond-containing group" refers to a group containing a carbon-carbon double bond that can undergo an addition reaction with a hydrogen atom bonded to a silicon atom by a well-known hydrosilylation reaction. Specific examples of the addition-reactive carbon-carbon double bond-containing group include alkenyl groups such as vinyl, allyl, 1-propenyl, isopropenyl, butenyl, hexenyl, and cyclohexenyl.

[0034] The component (b) is not particularly limited as long as it is a compound having at least one (meth)acrylic group and at least one addition reactive carbon-carbon double bond-containing group other than a (meth)acrylic group in one molecule and not having a polycyclic hydrocarbon skeleton. Specific examples include alkenyl (meth)acrylates such as vinyl (meth)acrylate, allyl (meth)acrylate, 1-propenyl (meth)acrylate, isopropenyl (meth)acrylate, butenyl (meth)acrylate, pentenyl (meth)acrylate, hexenyl (meth)acrylate, and cyclohexenyl (meth)acrylate, with allyl methacrylate represented by the following formula (5) being preferred. [ka]

[0035] <Addition reaction products> The component (A) is an addition reaction product obtainable by addition reaction of the above component (a) and component (b), and has one or more (meth)acrylic groups in one molecule.

[0036] As one example, it can be prepared by addition reaction, in the presence of a hydrosilylation reaction catalyst, of addition-reactive carbon-carbon double bonds in component (b) derived from groups other than (meth)acrylic groups, preferably in an amount of more than 1 mol and not more than 10 mol, more preferably more than 1 mol and not more than 5 mol, per 1 mol of Si-H groups in component (a).

[0037] In this case, known hydrosilylation catalysts can be used, and specific examples thereof include platinum metal-supported carbon powder, platinum black, platinic chloride, chloroplatinic acid, reaction products of chloroplatinic acid and monohydric alcohols, complexes of chloroplatinic acid and olefins, complexes of platinum chloride and alkenyl group-containing siloxanes, platinum-based catalysts such as platinum bisacetoacetate, platinum group metal-based catalysts such as palladium-based catalysts and rhodium-based catalysts, etc. The addition reaction conditions, the use of solvents, etc. are not particularly limited and may be as known.

[0038] The component (A) is not particularly limited, but is preferably one represented by the following general formula (6) or the following general formula (7), and particularly preferably one represented by R 1 is a methyl group, which is represented by the following formula (8) or (9).

[0039] [ka]

[0040] [ka]

[0041] [ka]

[0042] [ka]

[0043] The compound represented by the above formula (8) and the compound represented by the above formula (9) are addition reaction products of the compound represented by the following formula (3) or the compound represented by the following formula (4) as the above component (a) and the compound represented by the following formula (5) as the above component (b). That is, the component (A) is preferably an addition reaction product of the compound represented by the following formula (3) and / or the compound represented by the following formula (4) as the above component (a) and the compound represented by the following formula (5) as the above component (b). [ka] [ka] [ka]

[0044] [(B) Component] Component (B) is a polymerization initiator that polymerizes polymerizable functional groups such as (meth)acrylic groups in component (A), and as component (B), an organic peroxide that generates radicals by heat or a photopolymerization initiator that generates radicals by light such as ultraviolet light can be used. Among these, a polymerization initiator that generates radicals by ultraviolet light is particularly preferred.

[0045] (organic peroxide) As the organic peroxide, from the viewpoints of control of the storage stability and curability of the composition, as well as the heat resistance temperature of the quantum dots, an organic peroxide having a 10-hour half-life temperature of 50 to 150°C is preferred, and an organic peroxide having a 10-hour half-life temperature of 60 to 110°C is more preferred.

[0046] Specific examples of organic peroxides include benzoyl peroxide, t-butyl perbenzoate, o-methylbenzoyl peroxide, p-methylbenzoyl peroxide, di-t-butyl peroxide, dicumyl peroxide, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-ditetrabutylperoxy-cyclohexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne, 1,6-bis(p-toluoylperoxycarbonyloxy)hexane, di(4-methylbenzoylperoxy)hexamethylene biscarbonate, 2,5-dimethoxy-2,5-di(2-ethylhexanoylperoxy)hexane, and 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane.

[0047] Additionally, organic peroxides are commercially available, for example from NOF Corporation. Specifically, Perbutyl NHP (50.6), Perhexyl PV (53.2), Perbutyl PV (54.6), Peroyl 355 (59.4), Peroyl L (61.6), Perocta O (65.3), Peroyl SA (65.9), Perhexa 25 O (66.2), Perhexyl O (69.9), Nyper PMB (70.6), Perbutyl O (72.1), Nyper BMT (73.1), Nyper BW (73.6), Perhexa MC (83.2), Perhexa TMH (86.7), Perhexa HC (87.1), Perhexa C (90.7), Pertetra A (94.7), Perhexyl I (95.0), Perbutyl MA (96 .1), Perbutyl 355 (97.1), Perbutyl L (98.3), Perbutyl I (98.7), Perbutyl E (99.0), Perhexyl Z (99.4), Perhexa 25Z (99.7), Perbutyl A (101.9), Perhexa 22 (103.1), Perbutyl Z (104.3), Perhexa V (104.5), Perbutyl P (119.2), Percumyl D (116.4), Perhexyl D (116.4), Perhexa 25B (117.9), Perbutyl C (119.5), Perbutyl D (123.7), Permenta H (128.0), Perhexine 25B (128.4), Percumyl P (145.1), etc. The numbers in parentheses following the compound names above indicate their respective 10-hour half-life temperatures (unit: °C).

[0048] Of the above organic peroxides, from the viewpoints of compatibility with component (A) and the 10-hour half-life temperature, 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane (manufactured by NOF Corporation, Perhexa (registered trademark) 25O, 10-hour half-life temperature 66.2°C) is preferred.

[0049] These organic peroxides can be used alone or in combination of two or more.

[0050] The organic peroxide may be added in an effective amount, but typically, it is preferably 0.01 to 10 parts by mass, and more preferably 0.1 to 5 parts by mass, per 100 parts by mass of component (A).

[0051] (Photopolymerization initiator) Specific examples of photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propan-1-one, phenylglyoxylic acid methyl ester, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, etc. Commercially available photopolymerization initiators may also be used.

[0052] Of the above photopolymerization initiators, from the viewpoint of compatibility with the component (A), 2,2-diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one (Omnirad 1173 manufactured by IGM Resins BV), bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (Omnirad 819 manufactured by IGM Resins BV), and 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide (Omnirad TPO H manufactured by IGM Resins BV) are preferred.

[0053] These photopolymerization initiators can be used alone or in combination of two or more.

[0054] From the viewpoint of curability, the amount of the photopolymerization initiator added is preferably 0.1 to 10 parts by mass, and more preferably 1 to 5 parts by mass, per 100 parts by mass of the component (A).

[0055] [Other ingredients] The radical curing composition of the present invention may contain a known antioxidant such as 2,6-di-t-butyl-4-methylphenol in order to suppress the occurrence of coloration, cloudiness, oxidative deterioration, etc. of the cured product. In addition, a light stabilizer such as a hindered amine stabilizer may be added to impart resistance to photodegradation. Furthermore, if necessary, an inorganic filler such as fumed silica may be added to improve strength, or a dye, pigment, flame retardant, etc. may be added. An adhesive assistant (such as a silane coupling agent) may be added to improve adhesion.

[0056] The radical curing composition of the present invention may also contain a phosphor or quantum dots as a wavelength conversion material. Quantum dots are usually particles with an average particle size of 20 nm or less, and can absorb and convert light energy. The color of light can be adjusted by changing the particle size of the quantum dots. Since the band gap is determined by the particle size, light with high color purity can be obtained by regulating the particle size.

[0057] Quantum dots that emit in the visible light range include CdS, ZnSe, and CdSe-based particles with a shell such as ZnS. Cadmium-free quantum dots such as InP, CuInS2, AgInS2, Te, PbS, and InAs can also be used. Any type of conventional quantum dot can be used in the present invention.

[0058] As mentioned above, quantum dots generally contain catalytic poisons for the addition reaction, and therefore, when an addition-curing composition is used as a binder material for quantum dots, curing failure may occur. Furthermore, quantum dots have low heat resistance, so they are difficult to withstand the curing conditions of addition-curing materials.

[0059] On the other hand, the radical curable composition of the present invention can be cured at low temperatures (e.g., about room temperature) by radical curing, and therefore can avoid the above-mentioned problems that arise when an addition curable composition is used, and is useful as a binder material for quantum dots.

[0060] [Cured product] The present invention also provides a cured product obtained by curing the above radically curable composition.

[0061] The radically curable composition of the present invention can be cured at low temperatures by radical curing, and the cured product obtained by curing the radically curable composition of the present invention has excellent transparency and good hardness, and is therefore useful for applications such as encapsulating materials for LED elements and wavelength conversion filters.

[0062] In addition, when the radical curing composition of the present invention having a silphenylene skeleton or the like is used as a sealing material for optical elements, the resulting sealing material (cured product) has high gas barrier properties, so that it can prevent the intrusion of corrosive gas from the outside. It is also useful as a material for sealing quantum dots, which are sensitive to moisture.

[0063] The type D hardness of the cured product of the radically curable composition of the present invention is preferably 80 or more.

[0064] Furthermore, the cured product of the radically curable composition of the present invention preferably has a light transmittance of 80% or more at 400 nm in a thickness of 2 mm.

[0065] Such a cured product has high hardness and light transmittance and can therefore be preferably used as a sealant for optical elements, a wavelength conversion filter, or the like.

[0066] The hardness of the cured product can be measured, for example, using a durometer type D hardness tester in accordance with JIS K 6249: 2003. The 400 nm light transmittance of the cured product at a thickness of 2 mm can be measured, for example, by measuring the light transmittance of linear light having a wavelength of 400 nm using a spectrophotometer (e.g., U-3900 (manufactured by Hitachi High-Tech Science Corporation)).

[0067] [Curing method and conditions] Of the radical curing compositions of the present invention, the curing method and curing conditions of the thermal radical curing type containing an organic peroxide can be known. For example, the composition can be cured under a nitrogen atmosphere at 70 to 150°C for 10 minutes to 5 hours. In particular, when the polymerization initiator is an organic peroxide with a 10-hour half-life temperature of 50 to 150°C, it is preferable because it can be cured at a lower temperature.

[0068] Of the radical curing compositions of the present invention, known methods and conditions can be used as the curing method and curing conditions for the photoradical curing type, and the composition can be cured by irradiating light such as ultraviolet light. Examples of ultraviolet light sources include UVLED lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, metal halide lamps, carbon arc lamps, and xenon lamps. The irradiation amount (accumulated light amount) of ultraviolet light is preferably 1 to 10,000 mJ / cm for a sheet formed from the composition of the present invention to a thickness of about 2.0 mm. 2 and more preferably 10 to 9,000 mJ / cm 2 That is, the illuminance is 100mW / cm 2 When ultraviolet rays are used, the composition can be cured by irradiating the ultraviolet rays for about 0.01 to 100 seconds. EXAMPLES

[0069] The present invention will be described in detail below using examples, but the present invention is not limited to these examples. In the following, the viscosity at 25° C. was measured using a B-type rotational viscometer.

[0070] [Synthesis Example 1] In a 1L four-neck flask equipped with a stirrer, a condenser, a dropping funnel, and a thermometer, 69.5g (0.55 mol) of allyl methacrylate was dissolved in 118g of toluene and heated to 85℃ in an oil bath. 0.12g of a toluene solution of platinum hexachloride 1,3-divinyltetramethyldisiloxane (0.5% by mass in terms of platinum) was added to this, and 48.6g (0.25 mol) of 1,4-bis(dimethylsilyl)benzene was added dropwise while stirring. After the dropwise addition was completed, the mixture was stirred at 100℃ for 2 hours and then cooled to 25℃. Then, 1.4g of activated carbon was added and stirred at 25℃ for 1 hour, after which the activated carbon was removed by filtration, and the excess allyl methacrylate was distilled off under reduced pressure to obtain 100g of a colorless, transparent, oily addition reaction product (A-1) (viscosity at 25℃: 65mPa·s).

[0071] [Synthesis Example 2] In a 100mL four-neck flask equipped with a stirrer, a condenser, a dropping funnel, and a thermometer, 20.8g (0.17 mol) of allyl methacrylate was dissolved in 33g of toluene and heated to 85℃ in an oil bath. 0.03g of a toluene solution of platinum hexachloride 1,3-divinyltetramethyldisiloxane (0.5% by mass in terms of platinum) was added to this, and 12.6g (0.05 mol) of 1,3,5-tri(dimethylsilyl)benzene was added dropwise while stirring. After the dropwise addition was completed, the mixture was stirred at 100℃ for 2 hours and then cooled to 25℃. Excess allyl methacrylate was distilled off under reduced pressure to obtain 28g of a colorless, transparent, oily addition reaction product (A-2) (viscosity at 25℃: 220mPa·s).

[0072] [Examples 1 and 2 and Comparative Examples 1 and 2] The (A-1) and (A-2) components obtained in the above Synthesis Examples, or the (A-3) and (A-4) components for comparison were mixed with the following (B) component in the amounts shown in Table 1 (the numbers represent parts by mass), to prepare radically curable compositions.

[0073] (A) Component: (A-1) An organosilicon compound represented by the following formula (8), obtained in Synthesis Example 1 [ka] (A-2) An organosilicon compound represented by the following formula (9), obtained in Synthesis Example 2 [ka] (A-3) 1,4-bis(dimethylsilyl)benzene (compound represented by formula (3)) (A-4) 1,3,5-tri(dimethylsilyl)benzene (compound represented by formula (4))

[0074] (B) Ingredients: (B-1) Omnirad 1173 (manufactured by IGM Resins BV, photopolymerization initiator)

[0075] [Table 1]

[0076] The radical curing compositions obtained in the examples and comparative examples were irradiated with ultraviolet light having a wavelength of 365 nm at a dose of 4,000 mJ / cm under a nitrogen atmosphere at 25°C using an Eye UV electronic control device (model UBX0601-01) manufactured by Eye Graphics Co., Ltd. 2 The cured product having a thickness of 2 mm was evaluated by the following methods, and the results are shown in Table 2.

[0077] [Hardness] The hardness of the cured product was measured as type D hardness at 25°C.

[0078] [Light transmittance] The light transmittance of linear light having a wavelength of 400 nm at 25° C. was measured using a spectrophotometer U-3900 (manufactured by Hitachi High-Tech Science Corporation).

[0079] [Table 2]

[0080] As shown in Table 2, in Examples 1 and 2 using the radical curable composition of the present invention, the composition was cured by light irradiation at a low temperature in a short time, and had excellent hardness and transparency. On the other hand, in Comparative Examples 1 and 2 using compositions not having a (meth)acrylic group, no curing occurred under the above curing conditions. For this reason, the light transmittance was not measured.

[0081] Furthermore, it has been confirmed that the radical curable composition of the present invention has a higher hardness than the cured product of a conventional radical curable composition, even though it does not have a polycyclic hydrocarbon skeleton, which has been considered essential for increasing hardness in the past.

[0082] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.

Claims

1. A radical curable composition, (A) (a) a compound represented by the following general formula (2), (b) A compound having one or more (meth)acrylic groups and one or more addition-reactive carbon-carbon double bond-containing groups other than (meth)acrylic groups in one molecule, and having no polycyclic hydrocarbon skeleton. and a compound having one or more (meth)acryl groups in one molecule, (B) Polymerization initiator A radical curing composition comprising: 【Chemistry 1】 (In the formula, R 1 are independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms that does not contain an addition reactive carbon-carbon double bond-containing group, or an alkoxy group having 1 to 6 carbon atoms.

2. The radical curable composition according to claim 1, characterized in that the component (A) is an addition reaction product of a compound represented by the following formula (4) as the component (a) and a compound represented by the following formula (5) as the component (b): 【Chemistry 2】 【Chemistry 3】

3. 3. The radical curable composition according to claim 1, wherein the component (B) is a polymerization initiator that generates radicals when exposed to ultraviolet light.

4. A cured product obtained by curing the radical curable composition according to any one of claims 1 to 3.

5. 5. The cured product according to claim 4, wherein the cured product has a type D hardness of 80 or more.

6. 6. The cured product according to claim 4, wherein the cured product has a 400 nm light transmittance of 80% or more at a thickness of 2 mm.

Citation Information

Patent Citations

  • Photocurable silphenylene composition and cured material of the same

    JP2003327626A

  • Dental composition containing carbosilane polymer

    JP2008506816A

  • Curable composition, semiconductor device, and organic silicon compound containing ester bond

    JP2015147879A

  • Siloxane compound, and method of producing the same

    JP2019026606A

  • Addition-curable silicone resin composition, cured product of the composition and optical element

    JP2020128456A